Developing content to promote desistance in men who have committed intimate partner violence in same-sex relationships. (August 2019) - Morris, Jason; Gibbs, Charlotte A; Jonah, Omolara T; Bloomfield, Sinead; Weatherstone, Paul H; Ireland, Jane L
This article provides an overview of service development processes used to design a therapeutic approach that promotes desistance amongst men who have committed acts of Intimate Partner Violence (IPV) against their male partner or ex-partner. The article aims to explore how inclusive therapeutic service provision can be developed using the best available evidence, stakeholder consultation, co-production and technology. It does so by presenting a two-part study that draws upon a review of inclusive IPV theory alongside responses to a consultation designed to canvas stakeholder opinions (n = 14) of a proposed IPV service. It also provides a case study (n = 1) of the co-production of digital media with someone from the target group for that service. Implications for future service design for marginalised groups in the Criminal Justice System and provisions for people who have committed IPV are discussed. This article represents the views of the authors' and not those of Her Majesty's Prison and Probation Service (HMPPS).